A MODEL OF USING IPA FUNDS FOR PROJECT REALIZATION IN PRE-ACCESSION COUNTRIES: THE CASE OF SERBIA - Kranjac, Mirjana; Maksimović, Rado; Sikimić, Uroš (Ekonomika, 2010)
During the process of enlargement, the European Union established a mechanism to develop institutions and to support transition process in the EU, through financial help, for potential candidates and candidate countries. This foreign aid is operating throughout different EU funds. The instrument for the pre-accession assistance (IPA) has replaced all other financial funds for the budget period 2007–2013. The aim of this article is to give suggestions for a more efficient use of IPA funds. The article presents a case of Serbia by showing the empirical results from a questionnaire survey of 108 organizations evaluating a range of issues. A model of IPA funds’ use has been created. Risk points have been determined and divided into three groups: informing of potential beneficiaries, their education, and assistance in the realization of all project phases. Improvement could be achieved through the implementation of a new idea for setting up “project centres” which would support the process. Thus, civil society would be involved into the monitoring system.